Investigation on the position drift of the axis average line of the aerostatic bearing spindle in ultra-precision diamond turning. (September 2016) - Huang, P.; Lee, W.B.; Chan, C.Y.
Abstract: To evaluate the performance of the spindle, many techniques have been proposed to measure the spindle error motion. However, few studies have focused on the investigation of the position drift of the axis average line (AAL). In the present study, the AAL of the aerostatic bearing spindle is investigated both theoretically and experimentally. An error model is developed to analyze the errors which contribute to the error of depth of cut in slow tool servo assisted turning. Moreover, an experiment of microstructure fabrication is conducted to investigate the amplitude error of microstructures along both axial and radial direction of the cylindrical workpiece. The effects of spindle error motion, spindle unbalance induced eccentricity, thermal error and position drift of AAL are analyzed. The results indicates that the position drift of AAL varies significantly in terms of the variation of the spindle speed due to the hydrodynamic effect, and the relation between the drift and the spindle speed is nonlinear. Highlights: An error model is established to evaluate the cutting depth in S 3 machining. Errors which affect the actual depth of cut in S 3 machining are analyzed. The position drift of AAL due to hydrodynamic effect is verified. The angular drift of AAL is verified based on a cutting experiment.